2016
DOI: 10.1007/s00420-016-1171-1
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and occupational exposure to bisphenol A and endometriosis: urinary and peritoneal fluid concentration levels

Abstract: Results highlight the potential association between BPA exposure and endometriosis, as well as the current lack of knowledge regarding occupational exposure to BPA and the need of epidemiological studies focused on single activities/occupations, such as housewives, cleaners, students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 55 publications
1
35
0
1
Order By: Relevance
“…Furthermore, these findings were not confirmed by a subsequent prospective case-control study authored by Cobellis et al involving 11 healthy women aged 35-39 years and 58 women aged 33-39 years with endometriosis; in this study, urinary BPA levels were detected in 51.7% of 58 patients with endometriosis suggesting possible relationship between endometriosis and BPA [118]. In the same line are the results reported in a prospective case-control study carried out by Simonelli et al enrolling 60 women with endometriosis and 68 healthy women aged 30-40 years, in which higher urinary BPA levels were observed in women affected by endometriosis [119]. Focusing on ovarian endometriosis, Rashidi et al in a prospective case-control study on 50 Iranian women with endometrioma and 50 healthy women aged 32-37 years detected higher urinary BPA levels in patients with endometrioma [120].…”
Section: Observational Studies In Humanssupporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, these findings were not confirmed by a subsequent prospective case-control study authored by Cobellis et al involving 11 healthy women aged 35-39 years and 58 women aged 33-39 years with endometriosis; in this study, urinary BPA levels were detected in 51.7% of 58 patients with endometriosis suggesting possible relationship between endometriosis and BPA [118]. In the same line are the results reported in a prospective case-control study carried out by Simonelli et al enrolling 60 women with endometriosis and 68 healthy women aged 30-40 years, in which higher urinary BPA levels were observed in women affected by endometriosis [119]. Focusing on ovarian endometriosis, Rashidi et al in a prospective case-control study on 50 Iranian women with endometrioma and 50 healthy women aged 32-37 years detected higher urinary BPA levels in patients with endometrioma [120].…”
Section: Observational Studies In Humanssupporting
confidence: 86%
“…Several observational studies have been carried out to investigate the possible association between BPA exposure and the occurrence of endometriosis in humans [116][117][118][119][120][121][122]. The possible link between serum BPA levels and the occurrence of endometriosis has been firstly assessed by a prospective cross-sectional study in 2007 [116].…”
Section: Observational Studies In Humansmentioning
confidence: 99%
“…The hypothesis that exposure to bisphenols may enhance the risk of endometriosis risk is biologically plausible, as mentioned above. However, there has been little epidemiological research on this association to date, with an increased endometriosis risk reported by some authors [39,40] but no association by others [38,41]. This discrepancy may be attributable to differences in the criteria for selecting participants or in the timing of sample collections.…”
Section: Discussionmentioning
confidence: 99%
“…The present findings are in agreement with the study by Rashidi et al [37], who described an OR of 1.7 (95%CI 1.4-2.2) for the association between urinary BPA concentrations and endometriosis risk after adjustment for age, BMI, parity, and education, although urinary creatinine was not included as a covariate. Simonelli et al [40] also reported unadjusted associations between exposure and endometriosis, evaluated with the Student's t-test. This association is also supported by studies of mouse models of endometriosis, which related exposure to bisphenols in adulthood to increased endometriosis lesion growth and atretic oocyte number, disruption of the ovarian steroidogenic pathway, an increase in periglandular fibrosis, and the upregulation of matrix-remodeling enzymes [33,42].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, endometriosis symptoms are often associated with a significant impairment in psychological wellbeing [15,16], that has also a substantial impact on the quality of life [17,18]. Several different theories have been developed in order to justify the etiopathology of endometriosis; although the theory of retrograde menstruation [19,20], developed by Sampson, was widely accepted several years ago, to date, accumulating evidence suggests a key role of genetics, epigenetics, and immune mechanisms for the onset and progression of the disease [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%